Evolution of Protocols in Traditional Healing Practices and their Effects on the Practice of Healing - Cardinal, Clifford (Religious studies and theology, 2011)
Foremost in traditional views among Aboriginal people was the role of specially-gifted individuals, usually called medicine people (or, sometimes, shamans). Adapting this knowledge to the modern intellectual environment of medicine is a difficult but essential task. In this article, firsthand experience on these issues is explored through the work of a traditional healer who is also an Assistant Professor at the University of Alberta, Faculty of Medicine.